Child Protection in the Digital Age Through Education in the Islamic Educational Environment - Sholihah, Hani; Nurhayati, Sri (Letiges, 2024)
This study aimed to explore the efforts that Muslim families can take to prevent digital age risks and make education a tool of child protection in the digital age. This research used a literature research approach or literature study primarily on literature published within the last seven years. This research delineates six key findings: (1) the critical role of integrating Islamic values in education to navigate digital challenges, (2) the necessity of wise parental supervision in monitoring children's digital engagement, (3) the importance of educating children on digital security, (4) the challenges inherent in maintaining online safety for children, (5) the imperative of collaboration between parents and educators in digital age child protection, and (6) the centrality of education and digital literacy for both parents and children as foundational to child protection strategies in the digital landscape. The results are expected to guide Muslim families, educators, and other stakeholders on how education can be an effective protection tool for children in this digital age. By combining religious values, wise education, and the active role of parents, Muslim families can best protect their children in this rapidly evolving digital world.